Lattices Constructions for Euclidean Space Rn and its Subspaces - Hayyah, Zahira Najmatul; Kurniadi, Edi; Triska, Anita (Jambura Journal of Mathematics, 2026)
A lattice is a discrete subgroup of n-dimensional Euclidean space that serves as a fundamental object of study in Algebra and the Geometry of Numbers. This structure has significant applications in various fields, particularly in lattice-based cryptography and coding theory. This paper aims to present the formal construction of lattices for $n$-dimensional Euclidean space Rn and its linear subspaces by analyzing the formal definitions and essential properties of lattices. The main results of this research lie in two main results which are presented in several propositions. First, the set Zn of standard integer points is proven to be a lattice in n-dimensional space with respect to the standard basis of V \subseteq Rn. Second, the set of integer points whose last component is zero is proven to be a lattice within (n-1)-dimensional non-trivial subspaces. Indeed, in this case, the obtained lattice is not equal to Zn. Moreover, it also discussed the lattices of a non-standard basis for V. Explicitly, this work contributes a rigorous formal verification that integer structures within subspaces, such as Zn-1x0, retain fundamental lattice properties even under non-standard basis constructions.